2018
DOI: 10.5039/agraria.v13i1a5510
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium solani and F. oxysporum: Etiological agents of damping off in crambe

Abstract: ABSTRACT:The association of Fusarium sp. with agricultural seeds is a limiting factor for the uniform establishment of the crop. The aim of this work was to identify six isolates of Fusarium at the species level, based on morphological and molecular markers (TEF-1α and βtub); and to verify the pathogenicity of these isolates to the seeds of Crambe abyssinica (crambe). The pathogenicity test was carried out through the contact of the seeds with the fungal culture for 48 hours, followed by sowing in sand. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As a matter of consequence, the identification based on the sequencing of ITS region and others regions, such as EF-1α, has provided an alternative approach for higher detection and identification of Fusarium spp. [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of consequence, the identification based on the sequencing of ITS region and others regions, such as EF-1α, has provided an alternative approach for higher detection and identification of Fusarium spp. [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the pathogens that can infect soybean, Phytophthora sojae has been considered as one of the main causes of soybean damping‐off in southern Brazil (Costamilan et al, 2013) along with Rhizoctonia solani (Fenille et al, 2002) and Fusarium spp. (Migliorini et al, 2018). However, it has been reported that oomycetes belonging to the Pythium complex can also cause soybean damping‐off (Broders et al, 2007; Dorrance et al, 2004; Radmer et al, 2017; Rojas et al, 2017; Zitnick‐Anderson & Nelson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other pathogens such as Rhizoctonia solani (Fenille et al, 2002), Fusarium spp. (Migliorini et al, 2018) and Globisporangium/Pythium complex (Molin et al, 2021a) have also been associated with the disease. There is some information on the reaction of Brazilian soybean cultivars to R. solani (Ben, 2015) and Fusarium (Gásperi et al, 2003); however, little is known about their reaction to Globisporangium/Pythium species.…”
mentioning
confidence: 99%